SOME CHARACTERISTICS OF MENTAL ILLNESS, MENTAL DISORDER PREVENTION AND TREATMENT - Karshiyev Z.X; Tursunboyev A.U; Alkarov R.B. (Scholar Express Journals, 2022)
This article discusses mental illness, prevention of mental disorders and some of its features, as well as symptoms, cognitive disorders, measures to get rid of this mental illness and treatment.
Keywords: schizophrenia; depression; phobia; psychiatry